The use of flow behavior and thermal expansion to monitor structural change of amorphous Fe78Si9B13 ribbon - Niu, Y.C.; Bian, X.F.; Wang, W.M.; Jin, S.F.; Liu, X.J.; Zhang, J.Y.; Qin, G.L.
Samples of the amorphous Fe78Si9B13 ribbon were annealed isothermally and isochronally under different tensile stresses. These samples were also investigated using thermal expansion tests, DSC and XRD methods. The results show that a structural transition similar to the glass transition was found using thermal expansion method. Comparing the XRD patterns of the tensile stress annealed samples with those of stress free annealed samples, it is suggested that tensile stress promotes the crystallization.